Analisis Alignment Strategy PT Sari Husada Sebagai Bisnis Unit Danone Indonesia - , David Rinetyo Adhi ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Problems firm alliance with other companies one of them is the alignment between corporate strategy with business units. Thus corporate linkages with the business units need each other to one another, it takes good management of corporate strategy. The purpose of this study is to analyze the alignment strategy of PT Sari Husada at the strategic business unit with vision and mission of Danone. This study used a qualitative descriptive approach. Primary data using interview data were supported by secondary data such as annual sales reports, and other relevant supporting data. Analysis of data using analytical balance scorecards (BSC). The results of the study to obtain the alignment between PT Sari Husada as a business unit with Danone Group as a holding company. Alignment between PT Sari Husada by Danone Group formed from the vision and mission to the process line per line. With a good alignment between line per line in a business unit or the business unit with holding company, proven to maximize performance.